ENIGMA-Chronic Pain: a worldwide initiative to identify brain correlates of chronic pain: perspectives - Quidé, Yann; Jahanshad, Neda; Andoh, Jamila; Antoniou, Georgia; Apkarian, Apkar Vania; Ashar, Yoni K.; Badran, Bashar W.; Baird, C. Lexi; Baxter, Luke; Bell, Tyler R.; Blanco-Hinojo, Laura; Borckardt, Jeffrey; et al. (Pain, 2024)
An abstract is unavailable.
Gesehen am 15.04.2025